Placental polyp: a diagnostic dilemma - Ch, Sravani Chithra.; Manchanda, Rahul; Lekhi, Anshika; Jain, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Placental polyp is the retained fragment of placental tissue after parturition or abortion for indefinite period which forms a polypoidal mass in the uterus. It has an incidence of less than 0.25% of all pregnancies. It is predominantly composed of necrotic and hyalinized chorionic villi. These pedunculated masses present within days to weeks following an abortion or delivery of a term placenta. The patient presents with abnormal uterine bleeding and slightly elevated detectable titers of serum β-human chorionic gonadotropin (βHCG). Here we have reviewed the literature of placental polyp regarding its pathogenesis, diagnosis and management. The authors would like to stress the importance of hysteroscopy in diagnosis and management of placental polyp that can be missed on ultrasound and blind procedure like curettage and histopathology that gives a confirmatory diagnosis.